Reactor performance and economic evaluation of anaerobic co-digestion of dairy manure with corn stover and tomato residues under liquid, hemi-solid, and solid state conditions. (December 2018) - Li, Yangyang; Lu, Jiaxin; Xu, Fuqing; Li, Yu; Li, Danyang; Wang, Guoying; Li, Shuyan; Zhang, Hongyu; Wu, Yue; Shah, Ajay; Li, Guoxue
Highlights: Higher lipids and protein degradations were obtained at higher total solid (TS). Cellulose and hemicellulose reductions were not significantly affected by TS. Under analysis conditions, solid-state anaerobic digestion was financially attractive. The electric efficiency of CHP was the variable with the highest impact on NVP. Abstract: Anaerobic co-digestion of tomato residues, dairy manure, and corn stover at ratios of 20:48:32, 40:36:24, and 60:24:16 (volatile solid basis) were compared for liquid anaerobic digestion (L-AD), hemi-solid state AD (HSS-AD), and solid state AD (SS-AD) systems. The highest methane yield (353.5 L/kg-VSadded ) and volumetric methane productivity (24.5 m 3 methane /m 3 reactor volume ) were both obtained with 20% tomato residues addition under L-AD and HSS-AD conditions, respectively. Total solid and feedstock mixing ratio affected the degradation of protein and lipids during AD, but not cellulose and hemicellulose. Economic analysis results indicated that capital and labor costs have the dominant effect on total investment. SS-AD of tomato residues, dairy manure, and corn stover at ratios of 20:48:32 (VS basis) has the highest net present value (2.6 million US$) and shortest payback period (10.1 year), which indicated SS-AD was financially attractive under analysis conditions.